Keefektifan layanan informasi berbasis instagram untuk meningkatkan kepercayaan diri siswa - Akhmad Rifqi Azis; Prili Aprilia Salam (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
Students' interest in social media especially Instagram is very high, and makestudents able to expression in accordance with what they want. This research design uses experiment with one- group pre- test method and post- test design. The location of the research is SMP Negeri 1 Arjasa. Respondents of this research are student in junior high school, ages 13 years-15 years, which have Instagram accounts, and students who have low self-confidence. Data collected using questionnaires and documentation. The data taken is the test data validity, reliability test. Analysis method using product moment and t- test. From the test result using α = 5% paired sample t- test, and data used is 24 students before treatment (pre- test) and 24 students after treatment (post- test). Number of samples N = 24 students The results of this study indicate that Ha accepted and H0 rejected. From these results indicate that Instagram-based information service is effective to improve students' selfconfidence.